DESIGN AND BUILD A CAREER CENTER INFORMATION SYSTEM USING THE CODEIGNITER FRAMEWORK CASE STUDY AT UNIVERSITAS JENDERAL SOEDIRMAN USING WATERFALL METHOD - Muhammad Fikri Rivaldi; Lasmedi Afuan; Arief Kelik Nugroho (Jurnal Teknik Informatika (Jutif), 2022)
Universitas Jenderal Soedirman annually graduates thousands of qualified students. With so many graduates being issued, it is not uncommon for alumni to be confused about getting information about the world of work. Based on these problems, we need a place that accommodates all of them, namely the Career Center. Universitas Jenderal Soedirman has its own Career Center called Sudirman Career Center (SCC), which accommodating alumni to develop their careers. To do it all, SCC requires a computerized system that can help facilitate SCC in managing alumni data. This research aims to design a system that can make it easier for students, primarily alumni of Universitas Jenderal Soedirman, to find job vacancies and make it easier for agencies to manage their companies in the workforce. The data collection method used in this research is literature study, observation, and interviews, while the method for system development uses waterfall. The system design is done using UML. The programming language used is PHP combined with the Codeigniter framework and MySQL DBMS for data storage. From the research results, it can be concluded that alumni can use the existence of a web-based career center information system to obtain job vacancies information. Moreover, as a medium for the publication of each alumni's profile, it is easier for the SCC to manage alumni data and be helpful for agencies that need workers with various alumni backgrounds.